Understanding the InnerSource checklist : how to launch collaboration within your enterprise - Bonewald, Silona (O'Reilly Media, 2017)
Although many large corporations are reluctant to release the software they use in-house publicly as open source, those companies can still use principles and processes of open source for developing their in-house software--a practice popularly known as InnerSource. But adopting open source practices without understanding the cultural context behind them often fails. That's where this report comes in. Author Silona Bonewald explains how the InnerSource initiative, introduced by PayPal, can help your company develop software internally by applying lessons from the open source movement. A checklist guides you through various steps needed to produce open source software, whether it's companywide or just for one team. Alongside the how, Bonewald--Director of InnerSource Commons--also explains the why behind open source. You'll learn ways to improve collaboration, create cleaner code, reduce bottlenecks, and facilitate integrations among teams. This report examines: Ways to adapt InnerSource to your business environment without diluting open source fundamentals The crucial role of the Trusted Committer in the InnerSource process How to extracting tribal knowledge from silos through passive documentation Why contributing agreements formalize the responsibilities of developers who originate code How to move from internal silos to internal transparency.